الإدارة المستدامة للنباتات الطبية والعطرية ودورها في تحسين الدخل الريفي (Latakia University Journal -Biological Sciences Series, 2019)
تُعَدُ النباتات الطبية والعطرية من المحاصيل ذات القيمة النقدية العالية، ولاسيما عند زيادة القيمة المضافة لهذه المنتجات، إضافةً إلى لدورها في تأمين فرص عمل للسكان المحليين. هدف البحث إلى تحديد أهم الإجراءات المطبقة لزيادة القيمة المضافة، وقياس أثر هذه النباتات في تحسين دخل الأسر الريفية، إضافةً إلى تحديد الخصائص الاجتماعية والاقتصادية للعاملين القائمين بعملية جمع النباتات الطبية. أجريت الدراسة على عينة من القائمين بعملية جمع النباتات الطبية في محافظة اللاذقية للموسم 2009–2010، وذلك من خلال استمارة أعدت خصيصاً لهذا الغرض لعينة عشوائية قوامها 100 مفردة من السكان المحليين القائمين بعملية الجمع للنباتات الطبية. بينت النتائج أن متوسط عدد أفراد الأسرة العاملين في مجال النباتات الطبية 2 فرداً، وبلغ متوسط الدخل الشهري للأسر العاملة في النباتات الطبية (11486) ل.س/الأسرة، أي ما يعادل (1853) ل.س/الفرد. وقد تبين أهمية زيادة قيمة النباتات الطبية بعد إجراء بعض التحسينات عليها، فقد قام 60% فقط من المتعاملين بإجراء هذه التحسينات، بينما اعتمد الباقي على بيعها بشكلها الخام. واختلفت طبيعة هذه التحسينات على النباتات الطبية والعطرية ونوعها حسب نوع النبات، فشكَل التجفيف الإجراء الأساسي بنسبة 87%، يليه عمليتا الفرز والتنعيم بنسبة 5.6% لكل منهما، ثم الطحن بنسبة 5.6%. وقد شكَلت المشاتل المتخصصة بالنباتات الطبية مصدر الشراء الرئيس لهذه النباتات بأهمية نسبية بلغت  50%، يليها محلات العطارين بنسبة 19.3%، والباعة الجوالون بنسبة 18.1%، ثم المتعاملون بالطب التقليدي (العربي) بنسبة 9%، بينما انخفض التعامل مع المستهلك بصورة مباشرةً لتقتصر أهميته النسبية على 3.6% فقط. ويعد ارتفاع التكاليف التسويقية، وتشتت وضآلة الحيازات الزراعية، وعدم وجود هيئات متخصصة بتسويق محاصيل النباتات الطبية والعطرية، وعدم توفر الخبرة والمعلومات التسويقية، من أهم المشاكل التسويقية التي يعاني منها التسويق الداخلي لمحاصيل النباتات الطبية والعطرية. وخلصت الدراسة إلى أهمية إنشاء قاعدة بيانات ومعلومات لاستزراع النباتات الطبية وإنتاجها وتسويقها، وتنظيم الجمعيات التخصصية، وتوعية السكان المحليين بأهمية هذه النباتات والحفاظ عليها كمصدر مستدام للدخل. The study was conducted on a sample of collectors of medical plants in the province of Latakia for 2009 - 2010 season through a form specially prepared for this purpose a random sample of a 100 single of the local population collectors of medical plants, the goal of this research is to assess the processors conducted by local communities to maint medical plants, and measure the impact of these plants on household incomes, and the impact of  the social and economical characteristics of households on medical plant sustainability, in addition to  study the marketing chain for this plants. The average number of family members working in the field of plant Medical 2 individuals and the average monthly income of working families is11486sp per household, which is equivalent to 1853sp per person. Distributed sources of knowledge about the importance of medicinal plants by 14% from relatives and 58.7% and a tradition inherited from 27.3% during the growing market demand. And it increased the value of medicinal plants, after some improvements it has only 60% of customers make these improvements while the rest was adopted to sell the raw form. The Varied nature and type of these improvements on medicinal plants and aromatic plants depending on the type and form of the primary drying procedure by 87%, followed by the screening processes and smoothing by 5.6% each, and then grinding by 5.6%. Formed a nursery specialized medicinal plants as a buyer key to these plants relative importance of 50%, followed by shops Attarine rate of 19.3% and the street vendors by 18.1%, and dealers of traditional medicine (Arab) by 9%, while decreased to deal with the consumer directly to the limited relative importance of 3.6% only . The high marketing costs, dispersion and the small agricultural holdings, the lack of specialized marketing associations, medicinal and aromatic plants and lack of experience and marketing information of the most important marketing problems experienced by the internal marketing of crops, medicinal and aromatic plants. The study concluded that the importance of establishing a database and information for the cultivation, production and marketing of medicinal plants and re-organized professional associations and sensitize the local population to the importance of plants and maintain a sustainable source of income.